2021
DOI: 10.3390/atmos12020156
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship of a Low-Level Jet and the Formation of a Heavy-Rainfall-Producing Mesoscale Vortex over the Yangtze River Basin

Abstract: Dabie vortices (DBVs) are a type of heavy-rainfall-producing mesoscale vortices that appear with a high frequency around the Dabie Mountain over the Yangtze River Basin. For a long time, scholars have found that DBVs tend to form when a low-level jet (LLJ) appears in their neighboring regions. However, the underlying mechanisms of this phenomenon still remain vague. This study furthers the understanding of this type of event by conducting detailed analyses on a long-lived eastward-moving DBV that caused a seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Figure 5 further gives the distribution of differences in the simulated total precipitation (TP), convective (CP), and large‐scale precipitation (LSP) in each experiment relative to ERA5 in summer averaged during 1989–1999. As mentioned above, the ERA5 data have good accuracy in the Yangtze River Basin, China (Fu et al., 2021; Zhang et al., 2019) and provide large‐scale and convective precipitation data, which do not exist in gauge observation. From Figures 5a–5d, the differences in TP show very similar features to the gauge observations (not shown), indicating that the ERA5 data can be used to evaluate the model simulation (Chu et al., 2017; Kan et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 further gives the distribution of differences in the simulated total precipitation (TP), convective (CP), and large‐scale precipitation (LSP) in each experiment relative to ERA5 in summer averaged during 1989–1999. As mentioned above, the ERA5 data have good accuracy in the Yangtze River Basin, China (Fu et al., 2021; Zhang et al., 2019) and provide large‐scale and convective precipitation data, which do not exist in gauge observation. From Figures 5a–5d, the differences in TP show very similar features to the gauge observations (not shown), indicating that the ERA5 data can be used to evaluate the model simulation (Chu et al., 2017; Kan et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…To validate the outputs of RegCM4.6, we used the data listed as follows: (a) The fifth generation of ECWMF atmospheric reanalysis data (ERA5) with the horizontal resolution of 0.25° and temporal resolution of 24 hr from 1979 to the present (Copernicus Climate Change Service (C3S), 2017), which is available at https://cds.climate.copernicus.eu/cdsapp%23%21/search%3Ftype%3Ddataset. It has good accuracy in the Yangtze River Basin, China (Fu et al., 2021; Zhang et al., 2019). (b) The daily observed precipitation data set SURF_CLI_CHN_PRE_MON_GRID_0.5_V2.0, which is produced by interpolating the gauge‐observed precipitation at ∼2,400 stations over China from 1961 to the present with the consideration of GTOPO30 (Global Digital Elevation Model Data) topographic distribution onto the grids with the horizontal resolution of 0.5° (Zhao et al., 2014) (available at the site http://data.cma.cn/).…”
Section: Model Data Experiment and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [26] found that the sequential warm and cold Meiyu front regulated by the North Atlantic Oscillation was responsible for this abnormal Meiyu event. Fu et al [27] claimed that abnormally active mesoscale vortices and low-level jet acted as the direct reasons for a series of heavy rainfall events during the 2020 Meiyu season. The SCB and its surrounding regions were one of the most severely affected areas during the 2020 abnormal Meiyu season, and the SWVs were found to be one of the most important reasons for the torrential rainfall, lightning, and strong winds in this region.…”
Section: Conclusion and Discussionmentioning
confidence: 99%